Prognosis communication with older patients with multimorbidity: Assessment after an educational intervention - Schoenborn, Nancy L. (Gerontol Geriatr Educ, 2016)
OBJECTIVE: To assess how internal medicine residents incorporated prognosis to inform clinical decisions and communicated prognosis in primary care visits with older patients with multimorbidity after an educational intervention, and resident and patient perspectives regarding these visits. METHODS: Assessment used mixed-methods. We assessed the frequency and content of prognosis discussions through residents’ self-report and qualitative content analysis of audio-recorded clinic visits. We assessed the residents’ perceived effect of incorporating prognosis on patient care and patient relationship through a resident survey. We assessed the patients’ perceived quality of communication and trust in physicians through a patient survey. RESULTS: Twenty-one clinic visits involved 12 first-year residents and 21 patients. Residents reported incorporating patients’ prognoses to inform clinical decisions in 13/21 visits and perceived positive effects on both patient care (in 11/13 visits) and patient relationship (in 7/13 visits). Prognosis communication occurred in 9/21 visits by self-report but only in 6 of these 9 visits by content analysis of audio-recordings. Patient ratings were high regardless whether or not prognosis was communicated. CONCLUSION: After training, residents often incorporated patients’ prognoses to inform clinical decisions but sometimes did so without communicating prognosis to the patients. Both residents and patients reported positive perceptions regarding the visits.